2015
DOI: 10.1080/13607863.2015.1111863
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Emotion in relatives of persons with dementia: a systematic review and meta-analysis

Abstract: High-EE relatives were found to have increased levels of burden (Z = 6.967, P < 0.001) and greater levels of depression (Z = 5.842, P < 0.001). Compared to low-EE relatives, high-EE relatives were more likely to attribute the patient's problems to factors that were personal to and controllable by the patient. Relatives with less social support, inefficient coping strategies and a poor relationship with the patients, were more likely to be classified as high-EE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
1
37
2
Order By: Relevance
“…The tool has good reliability and validity (Armijo-Olivo, Stiles, Hagen, Biondo, & Cummings, 2012;Thomas, Ciliska, Dobbins, & Micucci, 2004). Consistent with other systematic reviews involving predominantly non-randomized studies (e.g., Safavi, Berry, & Wearden, 2015), the tool was amended to include five relevant rating domains: (a) Selection Bias; (b) Confounders; (c) Data Collection Methods; (d) Withdrawals and Drop-outs; and (e) Analysis (two of the four items). The original version of EPHPP does not include the Analysis domain in final ratings, and for consistency, this was also excluded from the adapted version.…”
Section: Key Practitioner Messagementioning
confidence: 99%
“…The tool has good reliability and validity (Armijo-Olivo, Stiles, Hagen, Biondo, & Cummings, 2012;Thomas, Ciliska, Dobbins, & Micucci, 2004). Consistent with other systematic reviews involving predominantly non-randomized studies (e.g., Safavi, Berry, & Wearden, 2015), the tool was amended to include five relevant rating domains: (a) Selection Bias; (b) Confounders; (c) Data Collection Methods; (d) Withdrawals and Drop-outs; and (e) Analysis (two of the four items). The original version of EPHPP does not include the Analysis domain in final ratings, and for consistency, this was also excluded from the adapted version.…”
Section: Key Practitioner Messagementioning
confidence: 99%
“…The term 'caregiver burden' is often used to describe this phenomenon, and it can be defined as "the degree to which a carer's emotional or physical health, social life or financial status have suffered as a result of caring for their relative" [12]. Caregiver burden increases the risk of depression and anxiety disorder [13][14][15][16][17], and informal caregivers of people with dementia living at home experience care as more burdensome compared to informal caregivers of recently institutionalized people with dementia [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we propose that caregivers who perceive stigma from their relative's illness may be more likely to be critical or intrusive (high EOI) toward their relative in an attempt to control symptomatic behaviors. We further hypothesized that high EE would partially mediate the link between stigma and quality of life (QoL) as there is some evidence that high EE is associated with poorer mental health in caregivers themselves (Safavi et al, 2015). In line with study hypotheses and using a sample of 106 dementia caregivers, we found that greater caregiver stigma was associated with both high EE (for criticism and EOI) and with poorer QoL.…”
mentioning
confidence: 53%